"Libraries motors of change" and the social role of (digital) libraries for their communities: Interview with IFLA President Glòria Pérez-Salmerón. Issue 3 (11th November 2019) - Coffa, Mario
Abstract : Purpose: Based on a comparison with different realities, analysis of the situation of libraries in line with International Federation of Library Associations and Institutions (IFLA) policies and directives. Design/methodology/approach: The method used for the following paper is that of a remote interview. Findings: The expected results will emerge from the debate that can be raised from this paper. Research limitations/implications: The IFLA guidelines have international value but are implemented according to the context of the individual country, not always in a uniform manner. Originality/value: The interview reveals the formality of the contents through the informality of the method.